Suggested Plan for Developing the Sources of Energy in Enviroment In Light Of Sustinable Development and the Affective Of Geographic Arabic Teacher (Journal of the College of Education for Women, 2019)
It is known that energy subiect has ocuppied a lot of scientests minds abouthow to treat the traditional energy and the renewing energy . we know thatmost traditional energy coal , oil , Natural gas, neuclear fuel , are limitedguantiy and alsow subjected to be ended .Statics studies refer to reserveof oil in world will exhausted btween ( 2075- 2100) and alsow cosl too .While neuclear fuerl which the world seek today through explod the uraniumatom ( 233) the therum atom (239) and neuclear mxied through ruemlearmixing , These energy have effect on environment and humanity speciaty ifthey are used in militery purposes .For all theses scientests srarch for resources of renewing enery throughresearches studies , using environment technology reduce traditional energy,they found that the resources of ernewing energy ( sun power , wind power ,mechanical power of water,chamical power of water , underland power,aidragyn power , natural power, laser power )The presnet study try to make suggestd plan to develop the resources oftraditional and contionuos energy and use them in arabic enviroment . Theresearcher found there is no plan for developing energy resources , he triedthrough this study to present infront of researchers and discuss the geogrphyteachers role who have the ability and srarch in natural resouces speciallythe resources of engery , through planning and developing these resourcesreaching to ( sustainable development ) which appear as a new concept fordevelopment and planning after 1997 by ( UN programm ) in developing theresources of humanity and nature and the right present and futuregeneration far away from ( poverty + ignorance + disease ) specially in arabicenviroment